A PRAGMATICS ANALYSIS OF ILLOCUTIONARY ACTS ON THE NARRATOR UTTERANCE IN MOBILE LEGENDS - Zainul Muttaqin; Moh. Gufron; M. Mizanul Haq (ELITERATE : Journal of English Linguistics and Literature Studies, 2026)
Language in digital games functions not only as communication but also as a mechanism that regulates interaction and gameplay dynamics. This study aims to investigate system-generated narrator utterances in Mobile Legends by identifying gameplay contexts, analyzing illocutionary act types, and examining the communicative functions conveyed through narrator utterances. This study employed a qualitative descriptive method using Speech Act Theory proposed by John Searle (1979) as the analytical framework. The data consisted of narrator utterances obtained from in-game gameplay in Mobile Legends Season 39 and Season 40, supported by gameplay videos from TikTok. The findings revealed that narrator utterances appeared across various gameplay contexts, particularly role excellence, mechanical skill, and survival kill streak contexts. In terms of illocutionary acts, representative acts were dominant, followed by expressive, directive, and declarative acts, while commissive acts were not identified in the data. Furthermore, narrator utterances functioned to inform, warn, command, motivate players, emphasize achievements, and regulate strategic responses during gameplay. These findings indicate that narrator utterances serve not only as informational announcements but also as communicative and regulatory mechanisms that organize gameplay interaction and support strategic coordination within digital gaming environments.